Catastrophic Antiphospholipid Syndrome with Severe Acute Thrombotic Microangiopathy and Hemorrhagic Complications. (9th December 2013) - Vieregge, Gerardo B.; Harrington, Thomas J.; Andrews, David M.; Carpintero, Maria F.; Green, Dollie F.; Nayer, Ali
Abstract : The catastrophic antiphospholipid syndrome (CAPS) is a rare life-threatening form of the antiphospholipid syndrome characterized by disseminated vascular thrombosis resulting in multiorgan failure. On an exceedingly rare occasion, CAPS can be associated with severe hemorrhagic manifestations. We report a young woman with a history of several spontaneous miscarriages who presented with menorrhagia and hemoptysis. The patient developed respiratory failure due to diffuse alveolar hemorrhage. Laboratory tests demonstrated severe hemolytic anemia, profound thrombocytopenia, markedly elevated fibrin degradation products, and renal failure. Blood films revealed numerous schistocytes. Serologic tests disclosed hypocomplementemia and autoantibodies directed against several nuclear antigens. Coagulation studies revealed lupus anticoagulant. Echocardiography demonstrated reduced ejection fraction and moderate to severe mitral and tricuspid regurgitation. The patient was diagnosed with CAPS with hemorrhagic manifestations in the setting of new-onset SLE. The patient was treated with hemodialysis, high-dose glucocorticoids, plasma exchange, intravenous cyclophosphamide, and rituximab. Over the ensuing four weeks, the combination therapy led to hematological, cardiopulmonary, and renal recovery. This exceedingly rare case emphasizes that hemorrhagic manifestations, severe microangiopathic hemolytic anemia, and profound thrombocytopenia can dominate the clinical picture in CAPS.